Under the over infrastructure for the spectacle of the everyday - Steynberg, Magriet (My University, 2016)
"Thresholds are often the most dynamic places in ecosystems. The cusp, both spatially and temporally, is the zone of maximum activity, exchange, hybridization and instability." (Kullmann, 2012) Threshold spaces, previously abandoned or unoccupied, have been infiltrated by various communities - the homeless occupy the undersides of bridges, traders fill pavements and foreign and rural migrants live in derelict buildings. People have created, through their bodies, areas of communication, encounter, and areas of commoning, through which the public 'square' or 'park' in Johannesburg can be reimagined, neither as public space nor as non-place, but rather as common space. It is here that architecture can engage with both the city and its user, space and experience. It is within public space, that architecture can both enhance and celebrate the spectacle everyday. This project investigates all of these aspects within the city of Johannesburg and more specifically along the threshold of the M1 Underpass (Henry Nxumalo Street), focusing on the Newtown Precinct. Programmatically a promenade and market is used to experience this spectacle.
Research report submitted to the school of architecture and planning in fulfillment of the requirements of the Masters of architecture (PROF) 2016
Keywords: City planning--South Africa; Newtown (Johannesburg, South Africa)